Morbillivirus Canis Infection Induces Activation of Three Branches of Unfolded Protein Response, MAPK and Apoptosis - Santiago Emanuel Colina; Macarena Marta Williman; Marco Antonio Tizzano; María Soledad Serena; María Gabriela Echeverría; Germán Ernesto Metz (Viruses)
Morbillivirus canis, commonly named Canine distemper virus (CDV), is a morbillivirus implicated in several signs in the Canidae family. In dogs (Canis lupus familiaris), common signs of infection include conjunctivitis, digital hyperkeratosis and neuropathologies. Even with vaccination, the canine distemper disease persists worldwide so the molecular pathways implicated in the infection processes have been an interesting and promising area in new therapeutic drugs research in recent years. It is known that in the process of virus infection, the endoplasmic reticulum (ER) loses its homeostasis, inducing stress and the subsequent unfolded protein response or UPR in which three ER-trans-membrane proteins are implicated: PERK, IRE1 and ATF6. Moreover, in prolonged ER stress, the apoptosis is induced through the CHOP, as a final step of viral infection. Cell culture and molecular techniques such as RT-qPCR and RT-PCR were used in the present study. We demonstrate the activation in vitro of the three UPR pathways after infection with an attenuated strain of CDV. Also, the implication of a MAPK pathway through the p38 protein and the apoptotic CHOP was demonstrated to contribute to the process of infection. Even more, our study suggested that CDV replication occurs in a PERK-dependent manner.